Shaking Table Test of Steel Cylindrical Liquid Storage Tank Considering the Roof Characteristics - Bae, Doobyong; Park, Jang Ho (International Journal of Steel Structures, 2018)
Steel cylindrical tanks are widely used for the storage of hazardous substances of which leakage must be prevented under any circumstances. However, the dynamic response of the steel cylindrical liquid storage tank depends sensitively on the fluid–structure interaction and the vibration of the tank structure and necessitates clarification for the safety of the tank structure. This paper presents the results of shaking table tests performed to examine the dynamic behavior of a scaled cylindrical steel tank model considering the presence or not of fixed roof and added mass at the top of the tank for various fluid levels. The test results confirm the occurrence of both beam-type and oval-type vibration modes and show that the larger content of liquid inside the container amplified the acceleration along the height of the cylindrical tank. The oval-type vibration modes are seen to be more dominant in case of large water-to-structure mass ratio.
Keywords: Cylindrical liquid storage tanks; Cylindrical tanks; Dynamic behaviors; Fluid level; Hazardous substances; Shaking table tests; Tank structure; Vibration modes; Dynamic behavior; Shaking table test; Steel cylindrical liquid storage tank; Vibration mode